Paper No P32: Synthesis and Characterization of a Solution‐Processable Hybrid Organic–Inorganic High‐k Dielectric for Low‐Voltage OFET Applications. (September 2013) - Verrelli, E.; Kemp, N.; O'Neill, M.; Cheng, F.; Alharti, F. A.; Kelly, S. M.
Abstract: In this paper, we describe preliminary steps in a new approach to make dielectric materials for low voltage monodomain organic field effect transistors to be used in backpanels for displays. A hybrid organic‐inorganic high‐k dielectric material based on oleic acid stabilized titanium oxide nanorods is synthesized and used to fabricate crossbar metal‐insulator‐metal capacitors in order to measure the dielectric properties of the hybrid dielectric. The hybrid dielectric has a high dielectric constant, of ∼8.1. A low parallel resistance is included in a model to explain the lossy behavior of the capacitors at frequencies below 1 kHz. Transistor characteristics and progress toward formation of a monodomain semiconductor will be presented.